Molecular cloning and expression study of proline-rich ena/vasp ligand 2a (PREL-2a) gene in zebrafish development - Chuo, Winnie (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Proline rich Ena/VASP Ligand 2 (PREL 2) is designated as Lamellipodin (Lpd) in mammals. PREL-2 possesses the ability to colocalize with Ena/VASP proteins at the tips of lamellipodia. Mammalian PREL-2 was found to have significant functions on cell signalling, direct migration, promoting axon guidance, affecting adhesion and regulating lamellipodial dynamics. Zebrafish PREL-2 gene is duplicated into two copies namely, PREL-2a and PREL-2b during a genome duplication event. The expression data of PREL-2 family only available for selected adult organs in human and mice but still no detailed information of PREL-2a in the embryonic stages. In this study, the cloning and expression profile of zebrafish PREL-2a gene was described. Semiquantitative RT-PCR analysis revealed that zebrafish PREL-2a gene is expressed throughout the development. PREL-2a gene expression was first expressed at 1K cells stage (3hpf) and constantly expressed throughout zebrafish development up to 5dpf. The RT-PCR result indicated that PREL-2a gene show maternal and zygotic expression.